The Relationship between Diagnostic Assessment and Student Motivation Aspects in the Merdeka curriculum - Arifin, Fikri (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2022)
This research has the purpose of describing the relationship between student motivation in diagnostic assessment in the independent curriculum. This research uses a descriptive qualitative method by collecting library data, reading and recording and processing research materials. The approach is intended to describe the objective conditions of the variables studied without any treatment of these variables. the results of this study that diagnostic assessment is closely related to student interest and motivation. Assessments that take into account variations in students' learning styles, interests and backgrounds can create an inclusive evaluation environment and motivate students to actively engage in the learning process. Thus, relevant learning contexts can be the key to increasing student motivation during diagnostic assessments under Merdeka Curriculum. Based on the research findings, it is recommended to align students' interests and motivation when formulating diagnostic assessments.